A Recovery Capital and Stress-Buffering Model for Post-deployed Military Parents - DeGarmo, David S.; Gewirtz, Abigail H. (Frontiers in Psychology, 2018)
We tested a recovery capital model for military families employing the ADAPT randomized control trial, a longitudinal preventive intervention study of 336 post-deployed military parents. Recovery resources included measures of social capital (parenting support, observed partner support behaviors), personal capital (parenting efficacy, education), and community capital (the ADAPT behavioral parent-training intervention). We hypothesized higher levels of recovery capital would buffer the negative impact of military stress on growth in PTSD symptoms for deployed and civilian parents. Outcome data were evaluated with three waves across two-years. Hypotheses were tested with latent growth models in a structural equation modeling framework. Military stress was assessed by reports of exposure to combat and battle aftermath. Recovery capital was measured reported support for parenting and direct observation of behavioral interactions during problem-solving discussions of deployment-related stressors. Fathers had higher levels of military related stress and PTSD symptoms over time compared to mothers. Growth curve models showed fathers were characterized by individual differences in 2-year average levels of PTSD symptoms while mothers were characterized by individual differences in initial status and linear growth trajectories. Results supported a recovery capital model. Higher levels of parenting efficacy and parenting support were associated with lower PTSD symptoms, representing common pathways for both mothers and fathers. Similarly, parenting support operated as a moderating buffer for both parents. That is, effects of military trauma exposure on psychological distress were lower for mothers and fathers with higher levels of parenting support relative to parents with lower levels. Regions of significance indicated that half a standard deviation above the mean of support was beneficial for mothers, while one and half standard deviations was needed to impact the effects of trauma on fathers’ PTSD. For mothers assigned to the ADAPT parent training intervention– but not fathers - the intervention was associated with linear reductions in PTSD symptoms over 2 years. The recovery capital model explained 36% of the variance in father outcomes and 46% for mothers. The intervention obtained a medium effect size in reducing mothers’ symptoms (d = .41). Implications for prevention and treatment within a recovery capital model are discussed.